1997
DOI: 10.1017/s0043887100008030
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights Violations, Umbrella Concepts, and Empirical Analysis

Abstract: Only in last decade or two have political scientists begun sys tematic, cross-national research on government violations of human rights. The primary research focus has been the rights associ ated with the "integrity of the person." At least two factors account for this relatively recent attention: the interest of President Jimmy Carter and Congress in setting human rights as a goal of American foreign policy and the publication of country-bycountry accounts of human rights performance by the U.S. Department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 9 publications
1
54
1
1
Order By: Relevance
“…We take up this challenge here and develop a model that explicitly assumes that repressive practices are related over time in that the pattern of abuses committed today might change the use of (or even the need for) future repressive actions for a certain period of time (Duvall and Stohl 1983;Stohl et al 1986). Our model is the first in the human rights literature to formalize this idea in the 3 See, for example , Brysk 1994;Donnelly and Howard 1988;Jabine and Claude 1992;Goodman and Jinks 2003;Lopez and Stohl 1992;Landman 2005;Landman and Carvalho 2009;McCormick and Mitchell 1997;Poe 1990Poe , 1991Poe, Carey and Vazquez 2001 and most recently Clark and Sikkink (forthcoming). Interested readers should also consult earlier papers from this debate, which are contained in Jabine and Claude (1992) and Claude and Jabine (1986).…”
Section: Measurement Of Human Rights Practicesmentioning
confidence: 99%
“…We take up this challenge here and develop a model that explicitly assumes that repressive practices are related over time in that the pattern of abuses committed today might change the use of (or even the need for) future repressive actions for a certain period of time (Duvall and Stohl 1983;Stohl et al 1986). Our model is the first in the human rights literature to formalize this idea in the 3 See, for example , Brysk 1994;Donnelly and Howard 1988;Jabine and Claude 1992;Goodman and Jinks 2003;Lopez and Stohl 1992;Landman 2005;Landman and Carvalho 2009;McCormick and Mitchell 1997;Poe 1990Poe , 1991Poe, Carey and Vazquez 2001 and most recently Clark and Sikkink (forthcoming). Interested readers should also consult earlier papers from this debate, which are contained in Jabine and Claude (1992) and Claude and Jabine (1986).…”
Section: Measurement Of Human Rights Practicesmentioning
confidence: 99%
“…Despite this minimal definition of democracy, Zakaria uses the maximalist Freedom House Political Liberties Index (Karatnycky 1999) as an operational measure for democracy and the Freedom House Civil Liberties Index as his measure of repression. McCormick and Mitchell (1997) have proposed a multidimensional indicator of human rights violations, one based on torture and killing and one based on imprisonment. They evaluate the relationship between these dimensions and democracy using the Vanhanen indicator.…”
Section: Some Steps Are Better Than Others: An Inverted-u Relationshipmentioning
confidence: 99%
“…Studies on repression have found that democracy and development are negatively related to repression and that domestic threats-armed internal and international conflict and protests-are positively related to repression (Poe and Tate 1994;McCormick and Mitchell 1997;Poe, Tate, and Keith 1999;Davenport and Armstrong 2004;Bueno de Mesquita et al 2005;Shellman 2006;Davenport 2007). 2 Thus, just as repression influences dissent, dissent influences repression.…”
Section: Repression and Dissent: Where The Media Come Inmentioning
confidence: 99%